Co-localised Raman and force spectroscopy reveal the roles of hydrogen bonds and π-π interactions in defining the mechanical properties of diphenylalanine nano- and micro-tubes - Sinjab, Faris; Bondakov, Georgi; Notingher, Ioan (American Institute of Physics, 2014)
An integrated atomic force and polarized Raman microscope were used to measure the elastic properties of individual diphenylalanine (FF) nano- and micro-tubes and to obtain quantitative information regarding the inter-molecular interactions that define their mechanical properties. For individual tubes, co-localised force spectroscopy and Raman spectroscopy measurements allowed the calculation of the Young’s and shear moduli (2565 GPa and 0.2860.05 GPa, respectively) and the contribution of hydrogen bonding network to the Young’s modulus (!17.6 GPa). The p-p interactions between the phenyl rings, dominated by T-type arrangements, were estimated based on previously published X-ray data to only 0.20 GPa. These results provide experimental evidence obtained from individual FF tubes that the network of H-bonds dominates the elastic properties of the FF tubes.